International cooperation - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1983)
Research activities carried out by CIAT in collaboration with national research institutions for the improvement of bean production in the Central American and Caribbean region are analyzed. In 1981, preliminary trials (EP) were planted in Costa Rica and Guatemala in an effort to identify promising materials in terms of tolerance to web blight (Thanatephorus cucumeris), BGMV, angular leaf spot (Isariopsis griseola), rust (Uromyces phaseoli), anthracnose (Colletotrichum lindemuthianum), and Ascochyta leaf spot (Ascochyta fabae). The international web blight nursery was assembled, being distributed to, and planted in, Costa Rica, El Salvador, Guatemala, Nicaragua, and Panama. The 1st international Apion nursery was also established; this nursery was planted in Guatemala, Honduras, and Mexico to develop commercially acceptable bean var. with resistance to the bean pod weevil (Apion godmani). All nonblack materials of the EP nursery were evaluated for resistance to BGMV in the Monjas site, Guatemala. (Extract)